OCE paper - Yu, Cerville Ang (Animo Repository, 2000)
The purpose of this term paper is to express concisely the strategies of Bank One and to propose how these strategies will be implemented to meet the objectives of the bank, in order for the bank to maintain its competitiveness in the thrift bank industry. This term paper utilized the models of McKinsey Consultants, Michael Porter's, and from the vast experiences of my professor Mr. Oscar Garcia occupying different positions from his numerous stints from companies both locally and internationally. Together with several financial institutions, banks are categorized to be in the financial services industry because of the very nature of their business that is to assist with the various financial needs and wants of their depositors. This varies from a simple deposit, request for a loan to more complicated investment opportunities available to the general public. Since the full liberalization of the banking industry many local and foreign investors have opted to enter the banking industry, thus greatly increasing the number of players. Profitability remains high in spite of huge capital requirement, high switching cost, and product differentiation among banks. Undoubtedly, entry barriers into the industry have been broken with the governments liberalized banking policy. Rivalries among banks have been so intense that a mere percentage point drop in interest rate would translate to a lost account for that bank. That is why banks are trying to develop new and better products to keep pace with the industry and have become more sensitive to customer needs. Opportunities, which the players in this industry could use on gaining a competitive advantage, include the strong government support, high liquidity in the market, healthy economic condition, advances in technology, product innovation, availability of skilled human labor. Unwavering Chamber of Thrift Bank support, Liberalized Policy, and LandBank Lines/Equity Investments. The threats in the industry includes, the liberalized policy, moratotium on opening of new branches, high level of non-performing loans, strong substitute products, termination of special tax breaks, high real and other property owned or acquired (ROPOA) and capital deficiency. Bank One Savings and Trust Corporation is a thrift bank with its Head Office located at #4201 Ramon Magsaysay Boulevard St. Mesa, Manila. It was registered with the Securities and Exchange Commission on April 11, 1997 to engage in the Savings and Mortgage Banking. The banks started commercial operations last August 1, 1997. The bank extend credit to commercial, industrial and consumer loans to both individuals and small and medium enterprises. Deposits are accepted in the form of demand, special savings and time. The bank likewise buys dollar notes and accepts dollar deposits and dollar time deposits but does not have dollar demand account. Strengths of the bank include professional managers, manageability, conservative, relatively well capitalized, lower operating expenses and affiliated with the Isetann Group of Companies and Gaisano. Weaknesses of the bank include branches are not on-line, new in the market, treasury location is outside the financial center, high net worth clients, limited products and excess liquidity. The banks vision is to be a major player in the industry. With its mission of mobilizing the small savings, provision of medium and long term credits to small and medium enterprises, provisions on housing loans and promotion of countryside development through financing in rural areas the bank would achieve its strategic objective. The bank will pursue a generic strategy of differentiation. The strategies are based on the opportunities and threats in the industry and environment and the company's strengths and weaknesses. The 7-S Framework by McKinsey Consultants was used for the implementation of strategies. The framework claims that effective organizational change is the relationship among structure, strategy, style, shared values, system, skills and staff. Change are therefore inevitable given the proposed strategies for the bank. These changes include acquisition of other thrift banks, evaluate, train and development employees, develop innovative and responsive products, streamline reporting system and control identity target market, improve on the both loan process and evaluation, cut down on time spent processing deposits and withdrawals, improve employees welfare and closely monitor the bank's branches.